Study of Variation in Activation Parameters in DMSO-H2O Media during Alkaline Hydrolysis of Ethyl Picolinate - Kumar Singh, Rajeev; Kumar, Kaushalendra (Asian Journal of Chemistry, 2010)
Variation in activation parameters during alkaline hydrolysis of ethyl picolinate was studied in DMSO-H2O media at different temperatures. The rate constant was found to increase with increasing percentage of DMSO indicating a somewhat less polar activated complex. Both iso-composition activation energy (Ec) and iso-dielectric activation energy (ED) for the above mentioned hydrolysis have been found to increase with increasing composition of DMSO. The variation in other activation parameters ΔS*, ΔH* and ΔG* have also been calculated and interpreted. The size of activated complex was also calculated complex was expressed by a new function NGe21b3. The stability of the activated complex was predicated by calculating the value of potential energy decrease in the activation process. have also been calculated and interpreted. The size of activated complex was also calculated to corroborate the above information. The polarizability of the activated complex was expressed by a new function ΣNGe2/b3. The stability of the activated complex was predicated by calculating the value of potential energy decrease in the activation process.